Proteolytic activities of human ADAMTS-5: comparative studies with ADAMTS-4. - Gendron, C; Kashiwagi, M; Lim, N; Enghild, J; Thøgersen, I; Hughes, C; Caterson, B; Nagase, H (2007)
Aggrecanases have been characterized as proteinases that cleave the Glu373-Ala374 bond of the aggrecan core protein, and they are multidomain metalloproteinases belonging to the ADAMTS (adamalysin with thrombospondin type 1 motifs) family. The first aggrecanases discovered were ADAMTS-4 (aggrecanase 1) and ADAMTS-5 (aggrecanase 2). They contain a zinc catalytic domain followed by non-catalytic ancillary domains, including a disintegrin domain, a thrombospondin domain, a cysteine-rich domain, and a spacer domain. In the case of ADAMTS-5, a second thrombospondin domain follows the spacer domain. We previously reported that the non-catalytic domains of ADAMTS-4 influence both its extracellular matrix interaction and proteolytic abilities. Here we report the effects of these domains of ADAMTS-5 on the extracellular matrix interaction and proteolytic activities and compare them with those of ADAMTS-4. Although the spacer domain was critical for ADAMTS-4 localization in the matrix, the cysteine-rich domain influenced ADAMTS-5 localization. Similar to previous reports of other ADAMTS family members, very little proteolytic activity was detected with the ADAMTS-5 catalytic domain alone. The sequential inclusion of each carboxyl-terminal domain enhanced its activity against aggrecan, carboxymethylated transferrin, fibromodulin, decorin, biglycan, and fibronectin. Both ADAMTS-4 and -5 had a broad optimal activity at pH 7.0-9.5. Aggrecanolytic activities were sensitive to the NaCl concentration, but activities on non-aggrecan substrates, e.g. carboxymethylated transferrin, were not affected. Although ADAMTS-4 and ADAMTS-5 had similar general proteolytic activities, the aggrecanase activity of ADAMTS-5 was at least 1,000-fold greater than that of ADAMTS-4 under physiological conditions. Our studies suggest that ADAMTS-5 is a major aggrecanase in cartilage metabolism and pathology.